Mathematics achievement among Malaysian students: What can they learn from Singapore - Ismail, N.A.; Awang, H. (2008)
Malaysia is ranked 16th and 10th in mathematics based on the Trends in Mathematics and Science Study (TIMSS) in 1999 and 2003 respectively, while its neighbor, Singapore used to be part of Malaysia until 1965, ranked first in both years. Hence, it is the aim of this study to investigate what makes Singaporean students better in Mathematics performance compared to Malaysian students. However, this study is limited to investigating factors that are collected by TIMSS in student, teacher and school background questionnaire. It is hoped that the findings from this study will provide useful inputs to improve mathematics learning among Malaysian students.